'People try and police your behaviour': the impact of surveillance on mothers and grandmothers' perceptions and experiences of infant feeding. (30th November 2018) - Grant, Aimee; Mannay, Dawn; Marzella, Ruby
Abstract : Pregnancy and motherhood are increasingly subjected to surveillance. Research has highlighted that public breastfeeding is difficult to navigate within existing constructs of acceptable femininity, but at the same time, mothers who formula feed are often located within discourses of the failed maternal subject. This article draws on intergenerational research with six mother/grandmother pairs from marginalised urban Welsh locales, which involved elicitation interviews around the everyday artefacts that participants presented to symbolise their experiences of motherhood and infant care. We examine the negotiation of acceptable motherhood in relation to the intrusive policing of lifestyle choices, consumption and infant feeding from family, friends and strangers. The article argues that the moral maze of surveyed motherhood renders infant feeding a challenging, and challenged, space for women.